2020
DOI: 10.1021/acs.jafc.0c01184
|View full text |Cite
|
Sign up to set email alerts
|

Urea-Based Low-Molecular-Weight Pseudopeptidic Organogelators for the Encapsulation and Slow Release of (R)-Limonene

Abstract: Low-molecular-weight compounds containing alkylurea fragments attached to the amino end of different miminalistic pseudopeptidic structures have been shown to be excellent organogelators in a variety of organic solvents and liquid organic compounds of different nature. The formation of gels in this work is defined through rheological measurements for those cases where G′ > G′′. Both the topology and the symmetry of the corresponding urea compounds play a role in defining their organogelator behavior. This can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Proteins have also been described such as zein (Bidyarani & Kumar, 2019), milk proteins (Sonu, Mann, Sharma, Kumar, & Singh, 2018) or others (Ansarifar et al, 2019). Synthetic polymers (Robayo, Sierra, & Perez, 2020), solid lipid nanoparticles (Angellotti et al, 2020), liposomes (Umagiliyage, Becerra-Mora, Kohli, well reported such as encapsulation in yeast cells (Normand, Dardelle, Bouquerand, Nicolas, & Johnston, 2005), calcium carbonate microparticles (Elabbadi, Jerri, Ouali, & Erni, 2015), or pseudopeptidic organogelators (Valls et al, 2020).…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Proteins have also been described such as zein (Bidyarani & Kumar, 2019), milk proteins (Sonu, Mann, Sharma, Kumar, & Singh, 2018) or others (Ansarifar et al, 2019). Synthetic polymers (Robayo, Sierra, & Perez, 2020), solid lipid nanoparticles (Angellotti et al, 2020), liposomes (Umagiliyage, Becerra-Mora, Kohli, well reported such as encapsulation in yeast cells (Normand, Dardelle, Bouquerand, Nicolas, & Johnston, 2005), calcium carbonate microparticles (Elabbadi, Jerri, Ouali, & Erni, 2015), or pseudopeptidic organogelators (Valls et al, 2020).…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Synthetic polymers (Robayo, Sierra, & Perez, 2020), solid lipid nanoparticles (Angellotti et al, 2020), liposomes (Umagiliyage, Becerra‐Mora, Kohli, Fisher, & Choudhary, 2017), metallic nanoparticles (de Barros, Cruz, Mayrink, & Tasic, 2018; Yang, Liu, & Liu, 2020), and composites with cyclodextrin derivatives (Saldanha do Carmo, Pais, Simplício, Mateus, & Duarte, 2017) have also been used to improve the pharmacological properties of the LIM. Others uncommon techniques have been as well reported such as encapsulation in yeast cells (Normand, Dardelle, Bouquerand, Nicolas, & Johnston, 2005), calcium carbonate microparticles (Elabbadi, Jerri, Ouali, & Erni, 2015), or pseudopeptidic organogelators (Valls et al, 2020).…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Supramolecular organogels have been attracting considerable attention over the last decades owing to their prospective and realized applications in numerous fields such as food, 1 , 2 cosmetics, 3 drug delivery, 4 6 encapsulation and controlled release of fragrance, 7 and advanced materials. 8 10 This kind of physical gel is generally formed by immobilizing organic solvents and oils in a three-dimensional network created by the entanglement of noncovalently self-assembled nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, C 2 -symmetric pseudopeptidic compounds displaying apolar spacers have shown remarkable gelating behaviours in different solvents [ 22 ], with the presence of additional functional components, such as urea fragments, significantly increasing the stability of the resulting supramolecular gels [ 23 , 24 ]. The introduction of polarfunctionalities in such pseudopeptides with apolar spacers has shown to afford efficient hydrogelators with pH-responsive self-assembling properties [ 25 ].…”
Section: Introductionmentioning
confidence: 99%